Islamic Higher Education, Its Dynamics and Role From Time to Time - Indra, Hasbi; Handrianto, Budi; Supraha, Wido; Rusydi, Ibnu (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
This research discusses the dynamics and role of Islamic higher education (IHE) until the present era. This era is distinguished by the ongoing development of science and technology, among other factors. IHE have undergone significant institutional and other developments, playing a pivotal role during the Old Order (ORLA), New Order (ORBA), and Reformation eras. Since its inception, IHE has been an integral component of the national education system, its significance further reinforced by two pivotal legislative acts: Law No. 2 of 1989 and Law No. 20 of 2003. Consequently, PTAI is obligated to contribute to the development of the nation while concurrently assuming responsibility for addressing its challenges across various domains. The nation is currently in a period of significant disruption, marked by economic challenges and a growing reliance on debt, which has now reached over 8000 trillion. This situation is further compounded by the presence of tens of millions of poor individuals and other pressing issues. In this context, PTAI is tasked with cultivating a generation of students who are not only well-versed in a broad array of disciplines, but also possess the qualities of entrepreneurship, competence, and moral integrity. This objective is to be achieved through the integration of moral and ethical principles into the educational curriculum, imparted by educators. Upon their graduation, these students will become valuable contributors to the nation's development.